2016
DOI: 10.1080/02699931.2016.1180280
|View full text |Cite
|
Sign up to set email alerts
|

The effect of spatial frequency information and visual similarity in threat detection

Abstract: In the current research, we sought to examine the role of spatial frequency on the detection of threat using a speeded visual search paradigm. Participants searched for threat-relevant (snakes or spiders) or non-threat-relevant (frogs or cockroaches) targets in an array of neutral (flowers or mushrooms) distracters, and we measured search performance with images filtered to contain different levels (high and low) of spatial frequency information. The results replicate previous work demonstrating more rapid det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…On the one hand, the behavioral data showed that participants avoided evolutionarily threatening information in the later stage of attention. Previous studies have shown that in the early stage of attention, individuals will focus their attention on evolutionarily threatening information 42 . In the later stages, individuals tend to avoid threatening information 43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, the behavioral data showed that participants avoided evolutionarily threatening information in the later stage of attention. Previous studies have shown that in the early stage of attention, individuals will focus their attention on evolutionarily threatening information 42 . In the later stages, individuals tend to avoid threatening information 43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…Theories of visual perception have suggested that the first stage of visual analysis includes the processing of spatial frequencies (e.g., Hegde, 2008;Kauffmann, Ramanoël, & Peyrin, 2014). Moreover, several studies have suggested that spatial frequencies play an important role in an effective detection-avoidance strategy (e.g., Bannerman, Hibbard, Chalmers, & Sahraie, 2012;Gao, LoBue, Irving, & Harvey, 2017). We showed that even when the phase information was scrambled, the trypophobic images elicited more discomfort than the fearful and neutral images.…”
Section: Discussionmentioning
confidence: 59%
“…In our view, the fact that the interactions between the origin of the background and the stimuli were specific to neutral targets suggest that threat itself has an advantage in processing as it is less sensitive to context, and other variables (Carretié et al, 2017; X. Gao et al, 2017). This effect has been shown consistently throughout both experiments.…”
Section: Discussionmentioning
confidence: 72%
“…Plenty of research (X. Mineka and Öhman, 2002; Öhman and Mineka, 2003; Isbister and White, 2004; Soares et al, 2009a, 2017; Gao et al, 2017) showed that these animals – especially snakes (Soares et al, 2009b, 2014; Gomes et al, 2017) – had been present as human species evolved, and posed as a real threat to our species. This suggests that fast and accurate detection of potentially lethal animals might have been under positive selection in the evolutionary past (but cf.…”
Section: Introductionmentioning
confidence: 99%